Ampulla of Vater metastasis from squamous cell carcinoma of the esophagus - Jun Hyuk Son; Jung Su Lee; Jong Wook Kim; Nam-Hoon Kim; Han-Seong Kim; Yoon Suk Lee (International Journal of Gastrointestinal Intervention, 2021)
Esophageal cancer is one of the lethal malignant tumors because it is often diagnosed in the advanced stage with lymph node or distant metastasis. The recurrence rate of esophageal cancer is known to be about 40% to 50% even in the patients who underwent curative esophageal resection. Most frequent sites of metastases are known to be the liver. Furthermore, other distant metastases also could be developed in lung, bone, brain, kidney, adrenal, abdominal cavity, and skin. However, ampulla of Vater (AoV) metastasis rarely occurs from esophageal cancer. Therefore, we report herein a case of AoV metastasis from squamous cell carcinoma of the esophagus.